AN ANALYSIS OF TEACHER’S TALK IN THE EFL CLASSROOM INTERACTION AT ABDURRAB FOUNDATION SCHOOL, PEKANBARU - Santoso Aguswan; Jismulatif (International Journal of Educational Best Practices, 2026)
This research aims to analyze types of Teacher's Talk, characteristics of Teacher's Talk, and patterns of interaction in the class in EFL learning at Abdurrab Foundation School, Pekanbaru, Indonesia. This research used observation classes, audio recordings, and semi- structured interviews with one English teacher. Three meeting classes from different classes were observed to ensure variation interactional. Data analysis used a deductive thematic approach guided by Flanders' Interaction Analysis Categories System (FIACS) and the concept of Classroom Interactional Competence (CIC). The research results indicated that asking and giving directions are the most frequent types of Teacher's Talk used, suggesting a pattern of teacher-centered learning. The absence of criticizing or justifying authority indicates that the classroom atmosphere was generally supportive and non-threatening. In terms of the characteristics of Teacher’s Talk, the teacher frequently employed questioning, scaffolding, and adaptive language to facilitate students’ understanding and participation. However, the use of extended wait time and opportunities for student–student interaction were still relatively limited. The classroom interaction patterns further revealed that teacher–whole-class interaction was dominant, whereas peer interaction occurred less frequently. These findings confirm the importance of maintaining a balance between instructional control and creating interactional space, particularly in EFL classrooms where increasing learner-centered participation is essential for communicative language development.